LEPTIN SEBAGAI INDIKATOR OBESITAS - Aladhiana Cahyaningrum (Jurnal Kesehatan Prima, 2015)
Abstract: Background: Obesity is a condition in which there is an excessive accumulation of body fat. Cases of obesity will continue to increase and an estimated 1.12 billion people in the world will be obese by 2030 (Meydani and Hasan, 2010; Der¬demezis et al., 2011). In Indonesia, the lifestyle changes that lead to Westernization causes changes in diet refers to a diet high in calories, fat and cholesterol that have an impact on the increased risk of obesity (Dir.Kes, 2009). Leptin is a protein derived from the 167 amino acids and the product of the obese gene (ob) with a molecular weight of 16 kDa that is synthesized mainly by adipose tissue. Leptin serves to regulate the metabolism of energy balance and body weight. In general, leptin plays a role in inhibiting hunger and increase energy metabolism. In individuals with large fat tissue contains more leptin than smaller fat tissue, whereas obesity is often found leptin resistance. Some researchers have found that higher leptin levels in obese people compared to people with normal weight (Considine, 1996). Circulating leptin levels in the blood of normal individuals known of 1-3 ng / mL, whereas circulating leptin levels in the blood of obese at 100 ng / mL (Hoda et al., 2012).